Preparação de nanopartículas de prata em meio alcoólico e utilizando moldes rígidos de silica mesoporosa - Oliveira, Roselaine da Silva [UNIFESP] (2014)
In this work the preparation and characterization of non-aqueous dispersions of silver nanoparticles (AgNP) prepared with 1-butanol, which acted as both solvent and reducing agent of Ag+ ions, obtained from silver nitrate or silver tetrafluoroborate were shown. A biocompatible block copolymer of polyether and polyamide (PEBA) was used as dispersion agent. The goal was to obtain non-aqueous dispersions of silver nanoparticle highly concentrated and stable. It is noteworthy to mention that in aqueous media, the silver nanoparticles concentration is relatively low (around 30 mg/L - 0.47 mM) and this dispersions does not show compatibility with hydrophobic surfaces such as PTFE, silicone, polyvinyl chloride (PVC) and polyethylene (PE). After finding the best experimental conditions (reactant concentration, type of silver salt, reaction time, percentage of stabilizer), it was produced a hydrophobic dispersion of silver nanoparticles, which is stable for more than 6 months, with a concentration of 5 mM, which is higher than that obtained in water. The AgNP diameters vary from 5 to 10 nm. The dispersion showed antimicrobial activity against Staphylococcus aureus and Escherichia coli even at low concentration. In addition, it was prepared and characterized silver nanoparticles immobilized into a mesoporous silica, called MCM-41 (with pores non-functionalized and functionalized surface with –SH and –SO3-), using 1-butanol as reducing agent of the silver ions, obtained from silver nitrate. 1-butanol was able to reduce the incorporated Ag+ in the silicas pores. A partial disordering of the silica has been observed mainly in the composite prepared with pure MCM-41. It was also found that there are silver nanoparticles inside the silica’s pores and the composite with –SH groups has the greater amount of silver. The catalytic activity of these composites was evaluated by the reduction of p-nitrophenol to p-aminophenol in the presence of sodium borohydride, but the MCM-41/Ag composite showed the highest catalytic activity for this test.